2013
DOI: 10.1016/j.neuroscience.2012.11.023
|View full text |Cite
|
Sign up to set email alerts
|

VMAT1 deletion causes neuronal loss in the hippocampus and neurocognitive deficits in spatial discrimination

Abstract: Vesicular monoamine transporters (VMAT) are involved in presynaptic storage and release of neurotransmitters. While it was thought initially that only VMAT2 is brain expressed and VMAT1 is present only in the periphery, recent data has challenged the exclusive expression of VMAT2 in brain. To further elucidate the role of VMAT1 brain expression and its potential role in neuropsychiatric disorders, we have investigated mice lacking VMAT1. Comparison of wildtype and knock-out (KO) mice using qPCR and immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
(79 reference statements)
2
13
0
Order By: Relevance
“…It may be worth noting that, aside from a smaller correlation of Slc18a1 with hour one infusions, neither one of these genes demonstrates an association with measures of self-administration behavior. Slc18a1, the vesicular monoamine transporter ( VMAT1 ), was originally thought to be only expressed in the periphery, however recent evidence has shown that VMAT1 may serve a role in the brain [26]. Deletion of Slc18a1 in mice reduces hippocampal neurogenesis and produces neurocognitive deficits [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be worth noting that, aside from a smaller correlation of Slc18a1 with hour one infusions, neither one of these genes demonstrates an association with measures of self-administration behavior. Slc18a1, the vesicular monoamine transporter ( VMAT1 ), was originally thought to be only expressed in the periphery, however recent evidence has shown that VMAT1 may serve a role in the brain [26]. Deletion of Slc18a1 in mice reduces hippocampal neurogenesis and produces neurocognitive deficits [26].…”
Section: Discussionmentioning
confidence: 99%
“…Slc18a1, the vesicular monoamine transporter ( VMAT1 ), was originally thought to be only expressed in the periphery, however recent evidence has shown that VMAT1 may serve a role in the brain [26]. Deletion of Slc18a1 in mice reduces hippocampal neurogenesis and produces neurocognitive deficits [26]. Furthermore mutations in the Slc18a1 gene also have been linked to an increased likelihood of developing schizophrenia [33] and type 1 bipolar disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…VMAT1 was initially thought to be expressed mainly in neurons of the peripheral nervous system and chromaffin cells, while the isoform, VMAT2, was thought to be expressed primarily in the brain [31, 32]. However, there is accumulating evidence that VMAT1 is also expressed in the brain where it plays important roles [3335]. Genetic variants of VMAT1 have been implicated in schizophrenia, bipolar disorders, autism, anxiety, depression, and neuroticism [34, 3639], suggesting that VMAT1 plays an important role in the evolution of psychiatric disorders and emotional behavior.…”
Section: Introductionmentioning
confidence: 99%
“…VMAT1 has recently emerged as an interesting new candidate gene, given its plausible neurobiological function and potentially distinct expression patterns in the brain during development and adult life (Hansson, et al, 1998). In preclinical studies, the deletion of VMAT1 in knockout mice results in a decrease in dopamine in the frontal cortex that translates behaviorally to cognitive deficits (Multani, et al, 2012). Furthermore, human genetic studies have found positive case-control associations between VMAT1 common missense variants and neuropsychiatric disorders, including bipolar disorder, schizophrenia, anxiety phenotypes and cognitive phenotypes related to schizophrenia, suggesting pleiotropy (Bly, 2005; Chen, et al, 2007; Lohoff, et al, 2006; Lohoff, et al, 2008a; Lohoff, et al, 2008b; Need, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%